Application of nanopigment watercolour fine art in painting. (30th September 2020) - Fang, Xi; Xu, Qian; Zeng, Cheng; Li, Xiao
With the development of science and technology and the development of watercolour paints, tools and techniques, watercolour as an independent art painting has gradually exerted its value in contemporary society. Aiming at the problems of small particle size, large specific surface area and large surface free energy of the nanopigment, and the possibility of agglomeration due to adsorption, the nanopigment was modified to make it exhibit its special properties. Experiments show that the larger the average particle size of the pigment, the larger the amount of water precipitation, and the worse the stability performance. As the viscosity of the pigment increases, the stability gradually increases, and then continues to decrease. Nano-Al2 O3 shows negative charge and can be well mixed with nano-SiO2 dispersion. The mixing process can be regarded as a process of mutual modification, and nanopigments with uniform dispersion, good stability and good compatibility can be obtained. Utilising the uncertainty and inclusiveness of the watercolour medium itself, and from the simple watercolour painting of painting techniques to the use of comprehensive materials to enrich the picture, the ideological pursuit is finally achieved. In the art creation, the artist needs to make the most of the characteristics of the material, combined with personal consciousness, to show his creative ideas as much as possible, so that the work is creative and expressive. With regard to how to use expanded materials and screen composition to achieve and enrich the expressiveness of artistic works, this paper starts from the theoretical basis of 'expression', demonstrates the course of expression, and advances the theory of expressiveness continuously. The abstract things are summarised into picture symbols, and the shape, colour, and picture composition of the picture, so as to enhance the expressiveness of the work, to achieve "art itself is the product of the artist's concept", and to make the artistic work more expressive.